2018
DOI: 10.11145/j.biomath.2018.12.167
|View full text |Cite
|
Sign up to set email alerts
|

A tribute to the use of minimalistic spatially-implicit models of savanna vegetation dynamics to address broad spatial scales in spite of scarce data

Abstract: The savanna biome encompasses a variety of vegetation physiognomies that traduce complex dynamical responses of plants to the rainfall gradients leading from tropical forests to hot deserts. Such responses are shaped by interactions between woody and grassy plants that can be either direct, disturbance-mediated or both. There has been increasing evidence that several vegetation physiognomies, sometimes highly contrasted, may durably coexist under similar rainfall conditions suggesting multi-stability or at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 94 publications
(207 reference statements)
2
33
0
Order By: Relevance
“…Previous modelling of the savanna biome using nonspatial ODE and impulsive differential equations models (see [100] for a review) has successfully identified a range of different mechanisms that stabilise species coexistence based on key differences between grasses and trees. Examples include disturbances that affect species asymmetrically, such as different functional responses in the description of grazing and browsing [84] or variations in the species' susceptibility to fires [101]; an age structure of trees with different competitive abilities of tree seedlings and adult trees [4,27]; or resource niche separation [92].…”
Section: Discussionmentioning
confidence: 99%
“…Previous modelling of the savanna biome using nonspatial ODE and impulsive differential equations models (see [100] for a review) has successfully identified a range of different mechanisms that stabilise species coexistence based on key differences between grasses and trees. Examples include disturbances that affect species asymmetrically, such as different functional responses in the description of grazing and browsing [84] or variations in the species' susceptibility to fires [101]; an age structure of trees with different competitive abilities of tree seedlings and adult trees [4,27]; or resource niche separation [92].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the consideration of spatial effects in the ecohydrological dynamics changes which species' intraspecific competition is responsible for species coexistence. In a nonspatial setting, a common approach to model coexistence of herbaceous and woody species in savannas [28], strong intraspecific competition of the (locally) superior species creates a resource niche for a second species and thus facilitates coexistence ( Fig. 3.1).…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, they particularly occur between 100 mm and 1500 mm (and sometimes more) of total mean annual precipitation (Lehmann et al [2011], Baudena and Rietkerk [2013]), that is along a precipitation gradient leading from dense tropical forest to desert. There is widespread evidence that fire and water availability are variables which can exert determinant roles in mixed tree-grass systems (Scholes and Archer [1997], Yatat et al [2018b] and references therein). Empirical studies showed that vegetation properties such as biomass, leaf area, net primary production, maximal tree height and annual maximum standing crop of grasses vary along gradients of precipitation (Penning de Vries and Djitèye [1982], Abbadie et al [2006]).…”
Section: Introductionmentioning
confidence: 99%
“…Along the rest of this gradient, rainfall is known to influence indirectly the fire regime through what can be referred to as the grass-fire feedback (Yatat et al [2018b], Scholes [2003] and references therein): grass biomass that grows during rainfall periods is fuel for fires occurring in the dry months. Sufficiently frequent and intense fires are known to prevent or at least delay the development of woody vegetation (Yatat et al [2018b], Govender et al [2006]), thereby preventing trees and shrubs to depress grass production through competition for light and nutrients. The grass-fire feedback is widely acknowledged in literature as a force able to counteract the asymmetric competition of trees onto grasses, at least for climatic conditions within the savanna biome that enables sufficient grass production during wet months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation